(untitled) (Forum Penelitian Agro Ekonomi, 2021)
Agricultural trade system in Indonesia, especially domestic market, is composed by nonformal relations among the actors. In imperfect market condition, social capital is fastly growing and become a backbone of the entire trade system. This paper is a study on social system of agricultural commodity market, its rules and the of the actors behind that system. The sources of information were gathered from a number of research reports on trade systems of several commodities and the actors who have specific roles in such systems.